The Basic Concept of KH. Ahmad Dahlan's Thoughts Influenced by the Middle Eastern Islamic Renewal Movement - juanto, Ade; Fajri, Muhammad Dwi; Sari, Zamah (CV. Raskha Media Group, 2026)
This study examines the basic concepts of KH. Ahmad Dahlan's (1868–1923) thought and its relationship to the ideas of the Islamic renewal (tajdīd) movement that developed in the Middle East in the late 19th and early 20th centuries, particularly the thought of Muhammad Abduh. Using a qualitative-historical approach (library research), a search of primary and secondary sources reveals that Ahmad Dahlan's key concepts—emphasis on the Qur'an and Hadith, encouragement of ijtihad and rejection of blind taqlīd, educational modernization, and the formation of social institutions—have a strong intellectual correlation with Middle Eastern renewal discourse, but have undergone a process of socio-cultural adaptation in the Indonesian archipelago. The implications of this study emphasize the role of literature, journals, and intellectual networks as channels for the transfer of ideas and recommend micro-historical studies to trace the routes of influence in more detail.